Pengembangan dan Penerapan Sistem Smart Office Berbasis Internet Of Things - Kevin Dwi Saputra; Raihan Ambari; Dio Ramadani; Tata Sutabri (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
To keep up with the times that have entered the digitalization era, the need for internet use is increasingly needed in various human activities, including the application of an Internet of Things (IoT)-based smart office system which is one of the breakthroughs in IT technology. There are some features that can be done as well as beneficial impacts to support worker activities through an internet-based smart office system. IoT is one of the technologies needed by many industries, from several large companies and startups, they have changed their workflows that tend to be conventional into smart offices. Currently, there are a lot of worker activities that have been integrated with various kinds of electronic media and internet networks to help them in their work.